2007
DOI: 10.3354/meps341103
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of ascidian sperm: two-dimensional patterns and short vs. time-integrated assays

Abstract: Understanding sperm dispersal patterns in free-spawning marine invertebrates is fundamental to assessing the likelihood of successful fertilization under a range of biological and physical conditions. Field estimates of sperm dispersal in egg broadcasters have relied on sperm assays that sample short-term sperm availability, and tended to focus on simple patterns of availability with distance along a 1-dimensional transect at a single site. However, sperm are diluted in multiple dimensions, and the decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…The levels of fertilization success in our study decreased drastically with sperm concentrations below 10 4 ml -1 , which agrees with the data available for several broadcast spawning marine invertebrates (see Pemberton et al 2003). However, most of the above-cited studies have not considered an extended period of egg longevity (Meidel & Yund 2001, Yund et al 2007). Nevertheless, the confounding effect of differences in sperm fertilization efficiency due to increased sperm concentration cannot be ruled out as a potential cause of the decrease in fertilization at high sperm concentrations.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The levels of fertilization success in our study decreased drastically with sperm concentrations below 10 4 ml -1 , which agrees with the data available for several broadcast spawning marine invertebrates (see Pemberton et al 2003). However, most of the above-cited studies have not considered an extended period of egg longevity (Meidel & Yund 2001, Yund et al 2007). Nevertheless, the confounding effect of differences in sperm fertilization efficiency due to increased sperm concentration cannot be ruled out as a potential cause of the decrease in fertilization at high sperm concentrations.…”
Section: Discussionsupporting
confidence: 90%
“…conducted with spermcast ascidians suggest that sperm availability declines with distance from the spawning point and is modified by depth and local hydrodynamic conditions (Yund et al 2007). In our study, naturally shed eggs of P. praeputialis were immersed at approximately equal depths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Johnson & Yund (2007) found that the estimate of the minimum number of males fertilizing broods of the tunicate Botryllus schlosseri did not vary between high and low density populations. Ayre & Miller (2006) reported genetic diversity that is consistent with multiple paternity in broods of a scleractinian in which colonies were scattered over several meters, and Yund et al (2007) found that fertilization of B. schlosseri eggs could occur over distances as far as 207 m.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 86%
“…However, Johnson & Yund (2007) found that the estimate of the minimum number of males fertilizing broods of the tunicate Botryllus schlosseri did not vary between high and low density populations. Ayre & Miller (2006) reported genetic diversity that is consistent with multiple paternity in broods of a scleractinian in which colonies were scattered over several meters, and Yund et al (2007) found that fertilization of B. schlosseri eggs could occur over distances as far as 207 m.The reproductive characteristics of Pseudopterogorgia elisabethae and studies of fertilization in marine invertebrates in general lead to the following questions about male spawning, which we address in this study: How variable is male reproductive success? Are males close to females more successful in siring larvae than males farther away?…”
mentioning
confidence: 99%